Elements of botany structural, physiological, systematical, and medical - Lindley, John 1799-1865 (Cambridge University Press, 2015)
Employed early in his career by Sir Joseph Banks, the botanist John Lindley (1799-1865) is best known for his recommendation that Kew Gardens should become a national botanical institution, and for saving the Royal Horticultural Society from financial disaster. As an author, he is best remembered for his works on taxonomy and classification. A partisan of the 'natural' system rather than the Linnaean, Lindley published this 1841 work, the fourth edition of his Outline of the First Principles of Botany, under a new title to emphasise not only that it was 'much extended, and, it is hoped, improved', but also that it was a textbook for students of 'structural, physiological, systematical, and medical' botany. He defines the different elements of a plant, and provides a checklist for identification of plant families, before discussing the various 'natural' systems of classification, including his own, and the different practical uses of plants.